Modulation of Pancreatic Tumor Potential by Overexpression of Protein Kinase C β1 - Cirigliano, Stéfano Martín (2013)
This study aimed to investigate whether the overexpression of protein kinase C β1 (PKCβ1) is able to modulate the malignant phenotype displayed by the human ductal pancreatic carcinoma cell line PANC1.